Disentangling community-based resource governance through knowledge systems mapping: insights from Community Fish Refuges in rural Cambodia - Baldivieso Soruco, C. R.; Bonatti, M.; de Silva, Sanjiv; Ou, P.; Soeun, K. O.; Neth, S.; Sun, V.; Rodríguez, T.; Sean, V.; Sithirith, M.; Dubois, Mark; Sieber, S. (Rural Development Institute (RDI) at Brandon University, 2025)
Inland fisheries in Cambodia are of great importance to the livelihoods of rural communities, as they provide sustenance and seasonal income for the local population. Community fish refuges (CFRs) are natural or human-made water bodies that hold water throughout the year, providing a dry-season sanctuary for aquatic life. Managed mainly by the local community, CFRs support diverse ecological and human functions, such as biodiversity repositories, including fish stocks, and provide water for irrigation, livestock, and domestic needs. These initiatives have been promoted by several organizations in Cambodia since the 1990s, showing positive ecological impacts and improving food security, especially for marginalized populations. However, the social dimensions of management, the role of local knowledge, and the underlying knowledge systems remain understudied. The objective of this study is to gain insight into the governance mechanisms of CFRs in relation to the local knowledge of management. Four CFR projects conducted by WorldFish and NGO partners between 2016 and 2021 in Central Cambodia were selected for the analysis. A participatory approach was employed using causal loop diagrams (CLDs) through focus group discussions (FGDs) with local stakeholders (n = 38). The methodological approach was based on three phases: exploratory interviews (n=23), causal-loop FGDs (n=4), and FGDs for data validation (n=4). Our study highlights the importance of context-specific and relational knowledge in CFR management, as well as the importance of institutional structures, power dynamics, and social differentiation in shaping knowledge access, distribution, and management. Social mobilization mainly involves village representatives mediating between villagers and external entities, with a certain degree of concentration of power within groups of stakeholders. Enhancing community governance through more inclusive, dialogue-based communication and potentially leveraging informal networks is recommended to channel social learning, considering the sociocultural context and challenges of decentralization in Cambodia.